(3Gdeage deG CTcd ef cJGH eSde (B( (3GdUMjM (B)s - (3CMeO Hf YeQ Hf EHQGgje GdbQWHj, CHh GdYHGS,J (B656 (3g` s ((3eMehO Hf YHO GdZaQ Hf jhSa Hf YHO GdYRjR Hf YeQ GdYLei s)
(3ChdgG (B:s
(3jHOC HHGH ChbGJ GdUdGI Hbhdg (B: (3HSe Gddg GdQMef GdQMje GdMeO ddg QH GdYGdejf bhdg Cf YeQ Hf YHO GdYRjR BNQ GdUdGI TjFkG s
(3BNQgG (B:s
(3jfJgi HHGH dGjSge ddfSGA Hbhdg (B: (3hefg bhdg JYGdi hSQGHjd Jbjce HGSe (B" (3hCUd GdHCS GdTOI hGdeTbI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG CQVg s
Keywords: (3GdMOjK h GdeUWdMs